Penerapan model team assisted individualization untuk meningkatkan hasil belajar matematika - Kundarwati, Nining (Indonesian Journal of Educational Development (IJED), 2020)
The purpuse of this reseach was to improve Mathematics learning outcomeson Trigonometric Identity Material inclass X MIPA 3 the students of SMA Negeri 1 Kedunggalar in semester 2 of the 2018/2019 academic year through the application of Team Assisted Individualization cooperative learning models. Subjects in the reseach were students of class X MIPA 3 of SMA Negeri 1 Kedunggalar in semester 2 of the 2018/2019 academic year by totaling 32 people. The object of the research was student learning activities and the Mathematics learning outcomes. Student learning outcomes data in Mathematics subjects were collected using tests. Data were analyzed using qualitative descriptive techniques. The research was result to be successful if it met criteria: (1) the average value of the minimum Mathematics TrigonometricI dentity Material test was KKM of 70, and (2) the classical completeness was at least 85%. The results of data analysis showed an increase in student learning outcomes in Mathematics Trigonometric Identity Material subjects inclass X MIPA 3 SMA Negeri 1 Kedunggalar after using the application of the Team Assisted Individualization type cooperative learning model. In cycle I, the average value of daily test was 66,38, and classical completeness was 72%, in cycle II the average value of daily tests was 75,00 with a classical completeness of 78%, and in cycle III the average value of daily tests was 81,88 with a classical completeness of 88%.Thus, the application of the Team Assisted Individualization type of cooperative learning model could improve student learning outcomes in Mathematics Trigonometric Identity Material learning after three cycles. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar Matematika materi IdentitasTrigonometri pada siswa kelas X MIPA 3 SMA Negeri 1 Kedunggalar Semester 2 tahun pelajaran 2018/2019 melalui penerapan model pembelajaran kooperatif tipe Team Assisted Individualization. Subjek dalam penelitian adalah siswa kelas X MIPA 3 SMA Negeri 1 Kedunggalar semester 2 tahun pelajaran 2018/2019 berjumlah 32 orang. Objek penelitian adalah aktivitas belajar dan hasil belajar. Data hasil belajar siswa dalam mata pelajaran Matematika dikumpulkan menggunakan tes. Data dianalisis menggunakan teknik deskripsi kualitatif. Penelitian dikatakan berhasil bila memenuhi kriteria: (1) nilai rata-rata ulangan Matematika materi Identitas Trigonometri minimal sebesar nilai KKM=70, dan (2) ketuntasan klasikal minimal 85%. Hasil analisis data menunjukkan terjadi peningkatan hasil belajar siswa pada mata pelajaran Matematika materi Identitas Trigonometri dikelas X MIPA 3 SMA Negeri 1 Kedunggalar setelah menggunakan penerapan model pembelajaran kooperatif tipe Team Assisted Individualization. Pada siklus I, nilai rata-rata ulangan harian mencapai 66,38 dan ketuntasan klasikal 72%, pada siklus II, nilai rata-rata ulangan harian mencapai 75,00 dengan ketuntasan klasikal sebesar 78% dan pada siklus III, nilai rata-rata ulangan harian mencapai 81,88 dengan ketuntasan klasikal sebesar 88%. Dengan demikian, penerapan model pembelajaran kooperatif tipe Team Assisted Individualization dapat meningkatkan hasil belajar siswa pada pembelajaran Matematika materi Identitas Trigonometri setelah dilakukan tiga kali siklus.